Asymmetric Information and Global Market Failure: Evidence and Policy Implications from Covid-19 - R. Pazhanisamy (Department of Humanities and Social Sciences (HSS), Jain University Global Campus, 2020)
The present pandemic covid-19 has changed the world in all the dimension of the human life. It has also changed the views of all discipline from individual attitude towards his health to the international trade. The life during the lockdown is an unforgettable experience to almost all in the world by creating defences in every walk of life for the survival. The time taken by the researched and scientist across the globe to invent the vaccine and its issues related to the general acceptability claimed the lives of many millions across the continents and still in the questions of how long will it take us in this journey. Everything is a product in economics. When there is global demand for the vaccine for the virus, how global market failed to provide it on time. This compels to make an enquiry into how the world market failed to react with appropriate vaccine invention and what theories are working in background for the present situation and how long will the world would be like this. What economic theories can be applied to make a solution under what constraints? There are very few attempts are only available on the interlink ages of this global market failure and the causes, policy remedies both at the gross root as well as at the macro level. In this context this paper is attempted to probe into this issue and fill the gap in research. Using the graphical approach first we have used the asymmetric information model for the accuses of market failure and then probed it towards the information's asymmetries and discover the combined impact on the Covid 19 policy response.
Additional information: Disclaimer: The views appeared in the works are of the authors only. In no way it reflects the institutions in which they belong to.
Keywords: D82; E30; E32; I38; J22; P11; 330; Market Failure; Coordination Failure; Asymmetric Information; Covid-19 and Global Market Failure; Policy Implication from Covid-19